2008
DOI: 10.1021/ci700388k
|View full text |Cite
|
Sign up to set email alerts
|

Docking of Noncompetitive Inhibitors into Dengue Virus Type 2 Protease: Understanding the Interactions with Allosteric Binding Sites

Abstract: A group of flavanones and their chalcones, isolated from Boesenbergia rotunda L., were previously reported to show varying degrees of noncompetitive inhibitory activities toward Dengue virus type 2 (Den2) protease. Results obtained from automated docking studies are in agreement with experimental data in which the ligands were shown to bind to sites other than the active site of the protease. The calculated K(i) values are very small, indicating that the ligands bind quite well to the allosteric binding site. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 36 publications
4
62
0
Order By: Relevance
“…Binding of ligands at the same pocket with different conformation may be due to changes of receptor specific conformation as explained by [35].…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
“…Binding of ligands at the same pocket with different conformation may be due to changes of receptor specific conformation as explained by [35].…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
“…Notably, DG is produced on-the-fly by a scoring function during the docking procedure. Besides the location of the pocket of primary ligands, numerous studies [11][12][13][14][15] have shown that the BD approach is useful in the solution of delicate problems such as the detection of subsidiary binding pockets containing e.g. exosites or allosteric binding sites.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical simulations about how cardamonin interacts with DV2 protease can also be found in literature. 90 …”
Section: Anti-infectious Activitymentioning
confidence: 99%